A Rational Approach to Organo‐Photocatalysis: Novel Designs and Structure‐Property Relationships. (27th October 2020) - Vega‐Peñaloza, Alberto; Mateos, Javier; Companyó, Xavier; Escudero‐Casao, Margarita; Dell'Amico, Luca
Abstract: Organic photocatalysts are emerging as viable and more sustainable tools than metal complexes. Recently, the field of organo‐photocatalysis has experienced an explosion in terms of applications, redesign of well‐established systems, and identification of novel scaffolds. A rational approach to the structural modification of the different photocatalysts is key to accessing unprecedented reactivity, while improving their catalytic performances. We herein discuss the concepts underpinning the scaffold modification of some of the most recently used photocatalysts and analyze how specific structural changes alter their physicochemical and redox properties. Abstract : No more trial and error! This Minireview outlines how a careful physicochemical properties analysis is instrumental towards the rational selection of a photocatalyst while delineating future applications and structural evolution.